COGNATE ACCUSATIVES: LOST IN TRANSLATION - Ayman Yasin (European Scientific Journal, ESJ, 2014)
This paper addresses the translation of cognate accusatives from Arabic into English by B.A senior students majoring in English language and its literature at the University of Jordan. The students translated (39) sentences containing the cognate accusative in a questionnaire prepared by the researcher for this purpose. The questionnaire included 3 different types of cognate accusatives: emphatic, type-identifying, and number identifying, as well as representatives of cognate accusatives and constructions that may be interpreted as having implicit cognate accusatives. Because of their semantic meaning and their complete absence in English, cognate accusatives were seen as redundant elements and thus were either non-existent in the students’ translations or were translated as intensifier adverbs. The paper, further,sheds some light on the syntax and semantics of the cognate accusatives and tries to account for the students’ different translations of these constructions. Moreover, the paper attempts to grasp some of the unconscious knowledge of native speakers through their preferences for translations of an Arabic structure that is totally absent in the target language (English).